Transcatheter Arterial Chemo Infusion (TACI) for Squamous Cell Carcinoma of the Tongue: A Case Report - Poedjomartono, Bagaswoto; Bangun, Alan Anderson; Frinces, Freshilla Sonia; Indrarto, Erwin Yudhistira Yasanusaraharja; Faiz, Ahmad (http://dharmais.co.id/, 2024)
Introduction: Cancers of the lip and oral cavity, with the tongue being the most common site, accounted for more than 377,700 cases and more than 177,700 deaths worldwide in 2020. Ninety percent of these oral neoplasms are squamous cell carcinomas (SCC). The main treatments for oral cancers are surgery, radiotherapy, and chemotherapy, either combined or as stand-alone therapies. Transcatheter Arterial Chemo Infusion (TACI) is considered the definitive treatment for locoregionally advanced squamous cell carcinoma of the oral cavity, aiming to preserve function after surgery while maintaining or improving locoregional control and survival rates. This case report presents the qualitative result of TACI on SCC of the tongue. The aim of this case report is to demonstrate the potency of TACI as an alternative palliative therapy for SCC of the tongue. Case Presentation: A 37-year-old man with SCC of the tongue was diagnosed and treated at Dr. Sardjito General Hospital, Yogyakarta in 2021. The patient underwent TACI procedure and subsequent radiotherapy sessions subsequently. The therapeutic response was evaluated by observing the clinical morphology of the lesions. Conclusions: TACI is a minimally invasive technique used in the management of SCC. TACI has shown its potency as an efficient and effective alternative palliative therapy.